2016
DOI: 10.1590/1806-9282.62.09.862
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of autologous fat grafting for the treatment of keloids and hypertrophic scars

Abstract: SUMMARY Introduction Since the 1980s, the use of autologous fat grafting has been growing in plastic surgery. Recently, this procedure has come to be used as a treatment for keloids and hypertrophic scars mainly due to the lack of satisfactory results with other techniques. So far, however, it lacks more consistent scientific evidence to recommend its use. The aim of this study was to review the current state of autologous fat grafting for the treatment of keloids and hypertrophic scars, their benefits and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Fat grafting has recently been explored as an adjuvant therapy for keloid and hypertrophic scars. 144 It has been shown to improve scar cosmesis and enhance tissue regeneration in burns patients with keloids. 145,146 The underlying mechanisms by which fat grafting augments scar quality are not clear.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Fat grafting has recently been explored as an adjuvant therapy for keloid and hypertrophic scars. 144 It has been shown to improve scar cosmesis and enhance tissue regeneration in burns patients with keloids. 145,146 The underlying mechanisms by which fat grafting augments scar quality are not clear.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…However, their translation into clinical application continues to be limited because of unresolved concerns related to safety, potential tumorigenicity, and effects on fibroblasts 103 . Autologous fat grafting is another method that is being tested because of the lack of adequate results with the current treatments available 104 . Silva and colleagues reviewed the studies of this treatment for hypertrophic scars and keloids 104 .…”
Section: Discussionmentioning
confidence: 99%
“…lipotransfer) for patients with keloids has been exemplified in several studies. [82][83][84] In three clinical cases, fat injection at the dermalhypodermal junction in hemifacial hypertrophic scars and keloids led to substantial improvement in skin texture, softness, thickness and elasticity after a six-month follow-up period. 82 Another study also demonstrated that autologous fat grafting in 18 patients with post-burn hypertrophic scars and keloids improved texture, colour, softness, thickness and elasticity of the treated skin.…”
Section: Fat Graftingmentioning
confidence: 98%
“…It seems that transfer of adipose tissue-derived stem cells (ADSCs) into wounds plays a key role in inhibiting keloid fibroblast proliferation and ECM formation. 84…”
Section: Fat Graftingmentioning
confidence: 99%